Association of sarcopenia with generalized anxiety disorder in Korean middle-aged and older adults: Results from the Korea National Health and Nutrition Examination Survey in 2022 - Hye-Eun An; Hye-Su Park; Chang Shik Yin (PLoS ONE, 2025)
We highlighted sarcopenia’s association with psychiatric disorders, including generalized anxiety disorder (GAD), and aimed to explore correlations between the detection and prevention of GAD using population-based data of middle-aged and older Korean adults. This cross-sectional study data was collected through standardized surveys and physical examinations including GAD assessment survey and sarcopenia examination through muscle strength and mass assessments. We used logistic regression analysis to examine the association between sarcopenia and GAD, adjusting for relevant confounders. Data from the 2022 Korea National Health and Nutrition Examination Survey (KNHANES) were analyzed for sarcopenia and GAD in individuals aged ≥40 years, employing the 2019 Asian Working Group for Sarcopenia criteria and GAD-7 scale, respectively. Overall, 2960 individuals were selected, focusing on sarcopenia and GAD-7 scores, and regression analyses explored sarcopenia and GAD associations. Notably, 3.7% and 14% of participants had sarcopenia and GAD, respectively. The relationships between sarcopenia, possible sarcopenia, and GAD were found for females, suggesting sex-specific risks. In females, after adjusting for marital status and smoking, sarcopenia and possible sarcopenia showed correlation coefficients (β) of 0.145 (95% confidence interval [CI]: 0.025–0.266) and 0.096 (95% CI: 0.004–0.189), respectively, with GAD. After further adjustment for physical activity variables, only sarcopenia remained significantly associated with GAD in females (β=0.132, P = 0.033). Sarcopenia was significantly associated with GAD severity. Individuals with sarcopenia were 1.051 times more likely to experience mild GAD (95% CI: 0.554–1.992) and 2.480 times more likely to experience moderate to severe GAD (95% CI: 1.232–4.990) compared to those without sarcopenia. This study found a significant correlation between sarcopenia and GAD in the examined demographics, emphasizing the importance of integrative physical and mental health interventions. Early detection and management of sarcopenia may contribute to GAD management, advocating a holistic approach to healthcare in aging populations.